Early mortality and overall survival in acute promyelocytic leukemia – a single-center experience - Krstevska Balkanov, Svetlana; Trajkova, Sanja; Genadieva Stavrikj, Sonja; Panovska Stavridis, Irina; Pivkova Veljanovska, Aleksandra; Stojanovska, Simona; Kocoski, Bozidar; Spasovski, Dejan (Macedonian Pharmaceutical Association, Ss. Cyril and Methodius University in Skopje, Faculty of Pharmacy, 2021)
Acute promyelocytic leukemia (APL) is a subtype of acute leukemia (AL) with distinct cytogenetics, clinical and biological characteristics. APL was considered as one of the most rapidly lethal forms of acute myeloblastic leukemia (AML), but recently, with the introduction of all-trans retinoic acid (ATRA) it has become the most curable subtype of AL. The main difficulty with APL is early death (ED), defined as death because of any cause within 30 days after diagnosis, and it has emerged as the most important cause of treatment failure. Our retrospective-prospective study was realized at the University Clinic for Hematology from January 2004 until December 2020. It included 46 patients with APL, according to FAB and WHO classification with confirmed molecular diagnosis. The following patients’ risk stratification factors were analyzed: age, Sanz risk score, WBC, PL, clinical presentation of the disease, levels of fibrinogen and Ddimers. During the study period, APL was diagnosed in 46 patients, 24 females (52.2%) and 22 males (47.8%), with mean age of 45 years. The overall survival showed that 24 patients (52.1%) were alive and 22 (47.8%) had lethal outcome. Regarding treatment, five patients (10.9%) died before starting the chemo-treatment. But, still, ED was observed in 13 patients (59%), and in 9 patients (40.9%) death occurred 30 days after establishing the diagnosis. The main reasons of mortality were also analyzed. To prevent ED prior to treatment, suspected APL patients should be immediately hospitalized and treated as medical emergency.
Keywords: acute promyelocytic leukemia; early death; all-trans retinoic acid